A Software upgrades investment model : a case of Windows operating system in Kenya. - Metto, Shadrack Kimutai (Strathmore University, 2008)
The revolution of software has introduced new actors and market mechanisms. Effective software management is crucial for development and survival of any company. IT upgrades investment in a crucial part in software management. The investments are usually costly and risky. Firms tend to treat such costs as operating expenses within the period incurred. Waiting too long may lead to lost competence, relevance and may prohibit a business from taking advantage of better vendor technologies in future, more so putting the company at risk by increasing the gap with the suitable business technology and business leadership opportunities. There are some factors which are critical in influencing the threshold point of change namely : acquisition and installation cost, change management (training and support), cost and opportunity cost. In context of both software and hardware upgrades, this project develops a simplified algorithm and tests its validity using data acquired from the Kenyan market to determine when is the appropriate time to upgrade where all costs are at minimum. The project focuses on study of Windows operating system.
Partial fulfillment for the award of Master of Science Degree in Information Technology
Keywords: Operating Software -- Management; Operating Systems -- Investment; Information Resource Management